GENETIC POLYMORPHISMS OF SERINE RACEMASE AND PROTEIN TYROSINE PHOSPHATASE RECEPTOR TYPE D ASSOCIATED WITH TYPE 2 DIABETES IN MALAY SUBJECTS - Saif-Ali, Riyadh (Universal Journal of Pharmaceutical Research, 2023)
Background and objectives: Serine racemase (SRR) and protein tyrosine phosphatase receptor type D (PTPRD) were suggested as Type 2 diabetes mellitus (T2DM) candidate genes by a genome-wide association study (GWAS) in the Chinese population. Association of SRR and PTPRD with T2DM have been reported among East Asian Populations. The association of SRR and PTPRD genetic polymorphisms with T2DM still needs to be studied in Southeast Asian Populations. Materials and Methods: This study aimed to evaluate the association of SRR and PTPRD genetic polymorphisms with T2DM in Malay subjects. The single nucleotide polymorphisms (SNPs) of SRR (rs4523957, rs391300, and rs8081273) and PTPRD (rs17584499 and rs649891) were genotyped in 440 T2DM and 398 normal Malay subjects. Results: The recessive genetic model showed that SRR genotype GG of rs4523957 and genotype TT of rs391300 are risk factors for T2DM (OR=1.42; 1.45, p=0.022; 0.020, respectively), whereas the dominant and additive genetic models showed that PTPRD SNPs rs17584499 were protective for T2DM (OR=0.76; 0.77, p=0.033; 0.031, respectively). Conclusion: This study replicated the association of SRR rs4523957, rs391300, and PTPRD rs17584499 genetic polymorphisms with T2DM in Malay, while more investigation in different populations is required to confirm this finding. Peer Review History: Received: 3 April 2023; Revised: 15 May; Accepted: 30 June 2023; Available online: 15 July 2023 Academic Editor: Dr. Amany Mohamed Alboghdadly , Ibn Sina National College for Medical Studies in Jeddah, Saudi Arabia, amanyalboghdadly@gmail.com Reviewers: Rola Jadallah, Arab American University, Palestine, rola@aauj.edu Dr. Dennis Amaechi, MrsFoluBabade Mini Estate , Flat 5 by Old Soldiers Quarter, Sabongari/Bwari, Abuja- Federal Capital Territory, Nigeria. amaechitoexcel@yahoo.com